Dynamic event‐triggered approach for networked control systems under denial of service attacks - Zhao, Ning; Shi, Peng; Xing, Wen (International journal of robust and nonlinear control, 2021)
This article studies the problems of exponential stabilization and ℒ2‐gain performance for networked control systems (NCSs) with transmission delays and periodic denial‐of‐service (DoS) attacks by exploring a resilient event‐triggered communication mechanism. First, a new resilient event‐triggered mechanism is developed to eliminate the adverse effects of network congestion caused by DoS attacks and decrease redundant communication so as to ensure efficient utilization of the limited network resources. The threshold parameter in the predefined event‐triggered condition can be adjusted according to the dynamic characteristics of the system. Then, an event‐driven control protocol is proposed, and a new switched NCS model is constructed. Sufficient conditions are then presented to ensure the exponential stability and ℒ2‐gain performance of the resulting closed‐loop system. Moreover, a co‐design scheme of the parameters in the event‐triggered condition and the controller gain is provided. Finally, the effectiveness and advantages of the new design techniques are verified through a comparative study for a robot manipulator control system.